Nanoscale topographic changes on sterilized glass surfaces affect cell adhesion and spreading. Issue 8 (30th September 2013) - Wittenburg, Gretel; Lauer, Günter; Oswald, Steffen; Labudde, Dirk; Franz, Clemens M.
Abstract Producing sterile glass surfaces is of great importance for a wide range of laboratory and medical applications, including in vitro cell culture and tissue engineering. However, sterilization may change the surface properties of glass and thereby affect its use for medical applications, for instance as a substrate for culturing cells. To investigate potential effects of sterilization on glass surface topography, borosilicate glass coverslips were left untreated or subjected to several common sterilization procedures, including low‐temperature plasma gas, gamma irradiation and steam. Imaging by atomic force microscopy demonstrated that the surface of untreated borosilicate coverslips features a complex landscape of microislands ranging from 1000 to 3000 nm in diameter and 1 to 3 nm in height. Steam treatment completely removes these microislands, producing a nanosmooth glass surface. In contrast, plasma treatment partially degrades the microisland structure, while gamma irradiation has no effect on microisland topography. To test for possible effects of the nanotopographic structures on cell adhesion, human gingival fibroblasts were seeded on untreated or sterilized glass surfaces. Analyzing fibroblast adhesion 3, 6, and 24 h after cell seeding revealed significant differences in cell attachment and spreading depending on the sterilization method applied. Furthermore, single‐cell force spectroscopy revealed a connection between the nanotopographic landscape of glass and the formation of cellular adhesion forces, indicating that fibroblasts generally adhere weakly to nanosmooth but strongly to nanorough glass surfaces. Nanotopographic changes induced by different sterilization methods may therefore need to be considered when preparing sterile glass surfaces for cell culture or biomedical applications. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 2755–2766, 2014.